2007
DOI: 10.1063/1.2591314
|View full text |Cite
|
Sign up to set email alerts
|

Spin-cast composite gate insulation for low driving voltages and memory effect in organic field-effect transistors

Abstract: The authors report on a solution-processed composite film based on poly(vinylidene fluoride/trifluoroethylene) copolymer and barium titanate (BT) nanopowder, to be used as ferroelectric high-κ gate insulation in organic field-effect transistors (OFETs). Flexible films of up to 50vol% BT powder content are produced by preparing homogeneous dispersion of the powder in the polymer solutions. The films exhibited high specific volume resistivities combined with dielectric constants of up to 51.5 at 1kHz. Low-voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…These explanations have also been brought up by the previous reports on the polarization behaviors of Ba 1−x Ca x TiO 3 ceramics. 14 With these supporting data, it is reasonable to illustrate the overall increase of polarization in Ba 1−x Ca x TiO 3 ceramics compared to that in BaTiO 3 .…”
Section: Ferroelectric Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…These explanations have also been brought up by the previous reports on the polarization behaviors of Ba 1−x Ca x TiO 3 ceramics. 14 With these supporting data, it is reasonable to illustrate the overall increase of polarization in Ba 1−x Ca x TiO 3 ceramics compared to that in BaTiO 3 .…”
Section: Ferroelectric Propertiesmentioning
confidence: 91%
“…[1][2][3][4] It is well known that BaTiO 3 undergoes the successive phase transitions from cubic to tetragonal (C-T), tetragonal to orthorhombic (T-O), and orthorhombic to rhombohedral (O-R), and its dielectric response and ferroelectricity primarily originate from the displacement of Ti ions, whereas the interaction of Ba in A-site and oxygen is ionic, which has no ferroelectric active component. 5,6 On the other hand, to improve the device performance and meet the continuing demand for further miniaturization of electronic devices using BaTiO 3 based materials, it is important to ensure the high dielectric constant, low dielectric loss, high remanent polarization and high dielectric strength.…”
Section: Introductionmentioning
confidence: 99%
“…A solution processed composite film of P(VDF-TrFE) and barium titanate (BT) has been also utilized as a gate dielectric layer in an organic FeFET with regioregular poly(3-hexylthiophene) (rr-P3HT) semiconductor. Yildirim et al argued that the composite films exhibited high specific volume resistivities combined with dielectric constants of up to 51.5 at 1 kHz and the FeFET fabricated operated at relatively low voltage with good memory retention [52]. The device properties demonstrated, however, seem to be questionable to justify the authors' claims properly.…”
Section: Metal/ferroelectric Polymer/insulator/semiconductor (Mfis) Amentioning
confidence: 71%
“…The programming voltage was reduced to 15 V by optimizing the ferroelectric layer deposition technique using cyclohexanone as a solvent, which results in thin, smooth and defect-free ferroelectric films. In 2007, Yildirim et al [92] obtained a high-k gate insulator by properly blending the P(VDF/TrFE) polymer solution with barium titanate nanopowder, and reported that the OTFT based on this composite gate dielectric showed low voltage consumption and good memory retention properties]. In recent years, tremendous progress has been achieved in ferroelectric OTFT memories, although there is still much to do in the practical application of nonvolatile ferroelectric OTFT memories.…”
Section: Structure and Fabrication Of Otft Memory Devicesmentioning
confidence: 99%
“…Currently, two methods are mainly used to fabricate OTFT memory devices, one of which uses ferroelectric materials, such as poly(vinylidene fluoride/trifluoroethylene) (P(VDF/TrFE)) [89][90][91][92] and nylon poly(m-xylylene adipamide) (MXD6) [93], or electret, such as polyvinyl alcohol (PVA) [94] and poly(-methyl styrene) (PMS) [95], which is chargeable as gate dielectric material. The memory function is implemented by the polarization of the ferroelectric material or the trapped charges in the electret, which modulate the channel conductance of transistors.…”
Section: Structure and Fabrication Of Otft Memory Devicesmentioning
confidence: 99%